Evaluation of Crack Propagation During Cyclic Bending of Wire Strip - Biallas, Alina; Merklein, Marion (Proceedings of the 14th International Conference on the Technology of Plasticity - Current Trends in the Technology of Plasticity, 2024)
Steel fibers applied as concrete reinforcement like in Ultra High Performance Concrete reduce the wall thickness and thus the amount of concrete [1]. The process chain notch rolling and cyclic bending presents the foundation of an ecologically and economically efficient approach for production of steel wire fibers. For fundamental perception of the characteristics and interdependencies of the innovative production method, analysis by experimental model processes is required. Previous research determined influence of various process parameters on crack propagation [2], which is further analyzed in this study. As testing material, a DP600 sheet metal (t0 = 0.8 mm) is applied. Cyclic bending tests of wire strip with staggered amounts of cycles and varying bending angles are performed and evaluated based on load curves and micrographs. The analysis supplies identification of stages of crack propagation, which allows recommendations for process design regarding controllability and geometry of fracture. For supporting the analysis, stamping and cyclic bending is numerically implemented in the simulation software LS DYNA to picture the present strain stage applied during bending. The process evaluation together with the built simulation model can later be used as reference for a suitable numerical modeling of crack propagation that will enable a more flexible analysis of the process chain and parameter effects by simulation.<br
Created from Fastlane, Scopus look-up
Keywords: Bending; Damage; Crack propagation